Trade Performance and Regional Integration of the CIS Countries - Freinkman, Lev; Polyakov, Evgeny; Revenco, Carolina (Washington, DC: World Bank, 2013)
The study provides a detailed quantitative analysis, based on standard econometric models, of the trends and the configuration of trade of the CIS countries, with an emphasis on its low income members. It also contains an analysis of the CIS countries' trade potential and its realization in a comparative perspective, as well as examination of the nature of the existing CIS intra-bloc trade. The study revealed no evidence that the CIS countries as a group underperform significantly in terms of either trade openness or export levels when compared to the countries of similar per capita GDP and population size. This means, however, that the low-income economies in the CIS (CIS-7) have been performing on average just marginally better than other low-income countries and that, overall, they have been falling behind the countries that benefit most from globalization. Overall, progress in the trade area was slower in the CIS-7 countries than in the higher income CIS members. This is reflected in: (i) lower overall export levels and slower export growth in the second half of the 1990s; (ii) higher trade deficits; (iii) lower share of manufacturing exports; (iv) incomplete re-orientation of trade flows from the CIS to global markets; and (v) lower incidence of intra-industry trade. The study found that the CIS free trade area is, on balance, a beneficial, trade-facilitating bloc. It features a free trade regime, agreements on mutual recognition of standards, and non-restrictive rules of origin. There is no evidence so far that the CIS integration is of the "South-South" type and thus may be harmful for some of its members. However, the potential benefits of CIS trade integration remain badly underutilized. The study suggests several directions for strengthening the legal and administrative framework for intra-CIS trade arrangements.